(untitled) (Malaysian Journal of Learning and Instruction, 2016)
Purpose – This paper presents the characteristics of effective literacy and numeracy teachers within the current context of teaching in Malaysia from the viewpoints of a sample of trained and experienced primary school teachers of literacy and numeracy. The characteristics were established based on what the teachers perceived as important in guiding their pupils, to equip themselves with the necessary literacy and numeracy skills in order to cope with imminent educational demands and challenges. Design – In this exploratory qualitative study, the data were collected in two phases. In Phase-1, the literacy and numeracy teachers individually responded to the Literacy Teacher Questionnaire (LTQ) and the Numeracy Teacher Questionnaire (NTQ) respectively. Both these questionnaires comprised open-ended questions. In Phase-2, focus-group discussions and reflection sessions, which focused on the teachers’ experiences in the primary schools’ literacy and numeracy teaching and learning processes, were carried out. The fully transcribed data from both the phases were thematically analysed. Findings – The findings indicated notable skills and characteristics of effective literacy and numeracy primary school teachers from the viewpoints of the teachers in the study. These characteristics were distinctively categorized into four main themes, namely (a) structure, (b) knowledge and understanding, (c) strategies and skills, and (d) values. Significance – The characteristics of effective literacy and numeracy primary school teachers that emerged from this study would serve as a frame of reference for education policy-makers and curriculum developers in determining the directions and plan of actions towards enhancing effective teaching and learning of literacy and numeracy in primary schools. The frame can also be adapted by teacher educators in aligning the training and learning activities with their literacy and numeracy trainees within their training institutions. Additionally, the findings of the study would serve as a flexible and adaptable foundation for improving the literacy and numeracy education of the Malaysian primary school pupils.